Employee performance management in NGOs through the non-physical work environment and psychological well-being: A systematic literature review - Deasy Rinayanti Pelealu (International Journal of Enterprise Modelling, 2026)
This study aims to analyze the interrelationship between the non-physical work environment, psychological well-being, and employee performance in nonprofit organizations (NGOs). NGOs operate under resource constraints and rely heavily on non-material approaches to manage employee performance. A Systematic Literature Review (SLR) using the PRISMA framework was conducted on articles indexed in Scopus, Google Scholar, and SINTA, published between 2015 and 2025. A total of 25 articles were selected and analyzed using thematic analysis. The findings show that the non-physical work environment—such as leadership, communication, and social support—has a significant impact on employee performance. Psychological well-being also plays a crucial role, both as a direct determinant and as a mediating variable linking the work environment to performance. In NGO contexts, intrinsic factors such as meaningful work and value alignment are more influential than financial incentives. This study offers novelty by providing an integrated synthesis that simultaneously examines these three variables within the NGO context, which has been largely overlooked in previous fragmented studies. Practically, the findings suggest that NGO managers should prioritize leadership development, strengthen internal communication, and design well-being-oriented policies to improve sustainable employee performance.